2022
DOI: 10.2196/38501
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Theory-Based mHealth Intervention on Disease Knowledge, Self-efficacy, and Exercise Adherence Among Ankylosing Spondylitis Patients: Randomized Controlled Trial

Abstract: Background Patient education is recommended as an integral part of disease management in ankylosing spondylitis (AS), a chronic rheumatic disease that predominantly affects young males and requires long-term disease management. Convenient and cost-effective approaches to deliver patient education are required to these patients. Objective This study aimed to examine the effects of a theory-based educational intervention delivered through a social network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Third, exercise self-efficacy was significantly higher in the experimental group than in the control group. This finding is consistent with the results of previous studies that have reported that the self-efficacy of an experimental group improved after participating in a mobile-based exercise intervention (Qin et al, 2022; Song et al, 2022). Self-efficacy is the belief in one’s ability to perform healthy behaviors (Bandura, 1977).…”
Section: Discussionsupporting
confidence: 92%
“…Third, exercise self-efficacy was significantly higher in the experimental group than in the control group. This finding is consistent with the results of previous studies that have reported that the self-efficacy of an experimental group improved after participating in a mobile-based exercise intervention (Qin et al, 2022; Song et al, 2022). Self-efficacy is the belief in one’s ability to perform healthy behaviors (Bandura, 1977).…”
Section: Discussionsupporting
confidence: 92%
“…Because establishing of reimbursed DHA with their high-quality standards is a specific German approach, direct comparison of Axia with international DTx is challenging. By reviewing Google Play Store, Apple App Store, and Pubmed, some axSpA-specific apps in Chinese-language could be identified with offering predominantly HbE-motivational interventions in contrast to Axia with HbE as direct intervention [ 22 , 23 ]. In English language, the Spondylitis Society of America (SSA) offers exercise videos on their homepage without providing an own DTx while the British National Axial Spondyloarthritis Society (NASS) has also published a DTx called “Back to Action” which provides HbE in the form of exercise videos [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It incorporates psychological and sociological concepts to examine individuals' attitudes and behaviors regarding health promotion, self-actualization, and fulfillment (Rosenstock, 2005). A study by Song et al (2022) demonstrated that using the Health Belief Model (HBM) in a WeChat-based educational intervention improved disease knowledge, self-efficacy, and exercise adherence in patients with Ankylosing Spondylitis. This study highlighted the feasibility and effectiveness of WeChat-based patient education for International Conferences ICT, Society, and Human Beings 2023;and e-Health 2023;Connected Smart Cities 2023;and Big Data Analytics, Data Mining and Computational Intelligence 2023 individuals with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%